Condición Física y depresión en Estudiantes Universitarios. Escuela Politécnica Nacional, 2019 - Buele Montaleza, Silver Lenin (2019)
This research is intended to analyze the physical condition and depression in students of the first semesters of Escuela Politecnica Nacinal. This research has the objective of determining the level of physical condition and depression of the university students. The types of research correspond to an analytical,field with a cross section and of cuali-cuantitatvo process. The population with which was worked thanks to the authorization of the authorities of the institution of higher education has a figure of 10,000 students, a non-random sample, consisting of 63 students of the first semesters of the different faculties, with 16 female students that reflects 24.2% of the sample and 47 male students that reflects 75.8% of the sample, the technique used was the survey, it was supported by a practical instrument that is the self-assessment questionnaire on physical condition and quality of life.in the presentation and discussion of results, the data obtained through of tabulation using the atatistical program SPSS 24 IBM, USA it was determined that the students are in an acceptable range with 1% and for the data collection for the variable depression, the questionnaire called the questionnaire of acale of DD by WWKZUNG where students are with moderate levels what is important to start university life.